Reviewing and Changing University Contributions to Development-Oriented Agricultural Research in Sub-Saharan Africa - Michelsen, Heike; Zuidema, Larry; Hoste, C. H.; Shapiro, D. (International Service for National Agricultural Research, 2003)
In an increasingly competitive world, universities cannot afford to be seen as purely academic institutions only; they are also expected to organize their considerable human and material resources in order to contribute materially to national research and development objectives. In sub-Saharan Africa it is especially important that universities participate fully in national agricultural research systems, becoming effective partners with national agricultural research organizations in promoting innovation. This briefing paper highlights the experience gained by ISNAR, the University of Hohenheim, and a number of African universities while implementing the project ""Strengthening the role of universities in national agricultural research systems in sub-Saharan Africa."" In 1994, agricultural research leaders in six countries in sub-Saharan Africa launched a far-reaching review-and-change program that looked systematically at factors limiting the effectiveness of agricultural research at their universities; since then they have designed and implemented action plans to address the constraints identified. In the course of the exercise, the project partners developed a systems perspective and a structured analytical framework that could also help research leaders elsewhere who face similar challenges. Research leaders considering embarking on a reform process of their own may obtain the relevant ISNAR study guide (Michelsen et al. 2003), which gives a detailed description of the procedures for a review-and-change process.